Civil Consumer Protection from Misleading Commercial Advertisements in the Internet Services Sector in Light of Newly Established Special Regulations - Abdalla Saeed Alketbi,; Mahmoud Ibrahim Mahmoud, (Journal of Legal Sciences, 2024)
This study aims to evaluate the role of the newly issued in the UAE in 2023 in addressing the gaps in general rules concerning misleading advertisements related to internet services. The research utilizes samples of these advertisements to examine their components and manifestations, assessing the adequacy of the general rules within the UAE Civil Transactions Law in protecting consumers from misleading advertisements. The study is divided into two sections: the first section defines Internet service contracts and highlights their key features, while the second section analyzes the elements and forms of misinformation in commercial advertisements for Internet services. It also evaluates the effectiveness of both general and special rules in combating these issues. The research concludes that the special provisions within the Consumer Protection Law and the regulations issued by relevant government agencies have successfully filled the gaps in the general rules, effectively curbing misleading advertisements. These special rules have contributed to reducing the prevalence of such ads by requiring prior approval from the Telecommunications Regulatory Authority and the UAE Digital Government for any commercial advertisement before it is published. Additionally, they mandate specific standards for the content of these ads, prohibit certain misleading phrases, and impose severe financial penalties on those who violate these conditions, including removing non-compliant ads from the market.